A pharmacokinetic drug interaction study between nebivolol and paroxetine in healthy volunteers. (21st May 2014) - Briciu, C.; Neag, M.; Muntean, D.; Vlase, L.; Bocsan, C.; Buzoianu, A.; Gheldiu, A.‐M.; Achim, M.; Popa, A.
Summary What is known and objective Nebivolol is a highly selective beta‐blocker with additional vasodilator properties, widely used in the clinical practice for the treatment of hypertension and heart failure. Paroxetine is a second‐generation antidepressant and a potent inhibitor of CYP2D6, the same isoenzyme involved in the metabolism of nebivolol. The objective of this study was to investigate the effect of multiple‐dose paroxetine intake on the pharmacokinetics of nebivolol in healthy volunteers and its potential consequences upon nebivolol pharmacodynamics. Methods The study included 23 healthy subjects and was designed as an open‐label, single‐centre, non‐randomized, two‐period clinical trial. During period 1 (reference), each volunteer received a single dose of 5 mg nebivolol, whereas during period 2 (test), each volunteer received a single dose of 5 mg nebivolol and 20 mg paroxetine, after a pretreatment regimen with paroxetine (20–40 mg/day for 6 days). The pharmacokinetic parameters of nebivolol and its active metabolite were analysed by non‐compartmental modelling. The pharmacodynamic parameters (blood pressure and heart rate) were assessed at rest, after each nebivolol intake. Results and discussion Pretreatment with paroxetine increased the mean peak plasma concentrations (Cmax) for unchanged nebivolol (1·78 ± 1·17 vs. 4·24 ± 1·67 ng/mL) and for its active metabolite (0·58 ± 0·21 vs. 0·79 ± 0·24 ng/mL) compared to nebivolol alone. The time (tmax) to reach Cmax was 1·37 ± 0·88 (h) and 3·11 ± 1·76 (h) for the parent compound and its active metabolite after nebivolol administered alone and 3·96 ± 1·76 (h), respectively, 7·33 ± 7·84 (h) after pretreatment with paroxetine. Also, the total areas under the curve (AUC0‐∞) were significantly increased from 17·26 ± 43·06 to 106·20 ± 65·56 h ng/mL for nebivolol unchanged and 13·03 ± 11·29 to 74·56 ± 88·77 h ng/mL for its hydroxylated metabolite, before and after paroxetine intake. All the pharmacokinetic parameters presented statistically significant differences when paroxetine was administered with nebivolol. Nonetheless, statistical analysis did not show a significant difference between the vital signs measured during the two periods. What is new and conclusion After pretreatment with paroxetine, the exposure to nebivolol was increased by 6·1‐fold for the parent drug and 5·7‐fold for the hydroxylated active metabolite. Paroxetine influenced nebivolol pharmacokinetics in healthy volunteers, but it did not have a significant effect on nebivolol pharmacodynamic parameters measured at rest, although the clinical relevance of this drug interaction needs further investigation.